Transshipment hub port selection criteria by shipping lines: The case of hub ports around the bay of Bengal - Chathumi Ayanthi Kavirathna; Tomoya Kawasaki; Shinya Hanaoka; Takuma Matsuda (Journal of Shipping and Trade (JST), 2018)
With the competitive nature of the liner shipping industry, the transshipment hub port selection process has become complicated with numerous decision-making criteria that need to be considered, and competition between hub ports has accelerated across different regions. The emergence of different liner service networks, such as "hub and spoke" and "relay", has also intensified the complexity of the hub port selection process. The overlapping of maritime markets simultaneously served by multiple competitive hub ports has offered various hub port choices for shipping lines. Therefore, the criteria for hub port selection for both hub and spoke and relay networks are separately discussed in this study, which evaluates the performances of four competitive hub ports located around the Bay of Bengal: Colombo, Singapore, Kelang, and Tanjung Pelepas. The hub port selection criteria are evaluated based on the monetary, time, port traffic, location, operation, and liner-related categories using a questionnaire survey administered to shipping lines. The results provide a detailed discussion on the significant criteria for both network types and also highlight the dominant performance of the Singapore port and the performance of the other hub ports based on the individual criteria.
Keywords: 650; Transshipment; Hub and spoke; Relay; Competitiveness; Selection criteria; Shipping lines